2006
DOI: 10.1007/s00421-006-0355-x
|View full text |Cite
|
Sign up to set email alerts
|

Central circulatory and peripheral O2 extraction changes as interactive facilitators of pulmonary O2 uptake during a repeated high-intensity exercise protocol in humans

Abstract: It has frequently been demonstrated that prior high-intensity exercise facilitates pulmonary oxygen uptake [Formula: see text] response at the onset of subsequent identical exercise. To clarify the roles of central O(2) delivery and/or peripheral O(2) extraction in determining this phenomenon, we investigated the relative contributions of cardiac output (CO) and arteriovenous O(2) content difference [Formula: see text] to the [Formula: see text] transient during repeated bouts of high-intensity knee extension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
(58 reference statements)
3
17
0
Order By: Relevance
“…This is the first study to investigate the relationship between cardiac vagal activity, normalV ˙ normalO 2 kinetics, and true Q ˙ kinetics within the same participants, the aim of which was to provide further insight into the mechanism(s) responsible for regulating normalV ˙ normalO 2 kinetics (Grassi, ; Hughson et al., ; Grassi, ; Hughson, ). This work extends those previous studies that have assessed the relationship between normalV ˙ normalO 2 kinetics and either true Q ˙ or HR (De Cort et al., ; Fukuba et al., ) or only the relationship between vagal withdrawal and HR kinetics (Javorka et al., ; Ricardo et al., ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is the first study to investigate the relationship between cardiac vagal activity, normalV ˙ normalO 2 kinetics, and true Q ˙ kinetics within the same participants, the aim of which was to provide further insight into the mechanism(s) responsible for regulating normalV ˙ normalO 2 kinetics (Grassi, ; Hughson et al., ; Grassi, ; Hughson, ). This work extends those previous studies that have assessed the relationship between normalV ˙ normalO 2 kinetics and either true Q ˙ or HR (De Cort et al., ; Fukuba et al., ) or only the relationship between vagal withdrawal and HR kinetics (Javorka et al., ; Ricardo et al., ).…”
Section: Discussionsupporting
confidence: 85%
“…Fukuba et al. () reported a similar contribution of true Q ˙ to the normalV ˙ normalO 2 response, accounting for 100% of the initial rise in normalV ˙ normalO 2 10 s after the step transition and 56% of the rise in normalV ˙ normalO 2 30 s after the step transition. Despite these values being similar to our findings, caution is required when interpreting the findings of Fukuba et al.…”
Section: Discussionmentioning
confidence: 83%
“…Accelerated systemic O 2 dynamics during exercise is associated with enhanced cardiovascular functions . Previous studies have reported that RIPC can enhance cardiac contractile capacity .…”
Section: Discussionmentioning
confidence: 99%
“…These previous findings suggest that the beneficial effect of RIPC on exercise performance may be associated with increased contractile capacity of the cardiac muscle. This enhanced cardiac contractile capacity may lead to the acceleration of systemic O 2 dynamics during whole‐body exercise . Furthermore, enhancement of whole‐body exercise performance is associated not only with the acceleration of local muscle O 2 dynamics but also with that of systemic O 2 dynamics .…”
Section: Introductionmentioning
confidence: 99%
“…Among these, increased muscle oxygen delivery may play a crucial role for its potentially direct effect (DeLorey et al 2007;Endo et al 2005;Faisal et al 2009), although enhanced activity of muscle oxidative enzymes and alterations of motor unit recruitment patterns have also been considered (for a review of these alternative hypotheses, see Poole and Jones 2012). According to Faisal et al (2009), greater oxygen delivery with increased leg blood flow after prior heavy exercise (Fukuba et al 2007), or an elevation in pyruvate dehydrogenase and intracellular lactate and acetyl CoA concentrations (Gurd et al 2006), may generate an increase in PO 2 following elevated oxygen delivery.…”
Section: The Effect Of Priming Exercisementioning
confidence: 97%